A morphology independent approach for identifying dividing adult neural stem cells in the mouse hippocampus. Issue 1 (2nd August 2017) - Harris, Lachlan; Zalucki, Oressia; Oishi, Sabrina; Burne, Thomas H.; Jhaveri, Dhanisha J.; Piper, Michael
Abstract : Background : Type 1 adult hippocampal neural stem cells (AH‐NSCs) continue to generate neurons throughout life, albeit at a very low rate. The relative quiescence of this population of cells has led to many studies investigating factors that may increase their division. Current methods of identifying dividing AH‐NSCs in vivo require the identification and tracing of radial processes back to nuclei within the subgranular zone. However, caveats to this approach include the time‐intensive nature of identifying AH‐NSCs with such a process, as well as the fact that this approach ignores the relatively more active population of horizontally oriented AH‐NSCs that also reside in the subgranular zone.Results : Here we describe, and then verify using Hes5 ::GFP mice, that labeling for the cell cycle marker Ki67 and selection against the intermediate progenitor cell marker TBR2 (Ki67 +ve ; TBR2 −ve nuclei) is sufficient to identify dividing horizontally and radially oriented AH‐NSCs in the adult mouse hippocampus.Conclusions : These findings provide a simple and accurate way to quantify dividing AH‐NSCs in vivo using a morphology‐independent approach that will facilitate studies into neurogenesis within the hippocampal stem cell niche of the adult brain. Developmental Dynamics 247:194–200, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: This paper provides a quick, reliable and reproducible method to accurately identify adult hippocampus neural stem cells.